Exposure to Bullying Among Adolescents Across Nine Countries - Yoke, Yong Chen; Ask, Elklit (Springer International Publishing, 2018)
Bullying is not included in Diagnostic and Statistical Manual for Mental Disorders (DSM) criteria (Criteria A, APA, 2013) for posttraumatic stress disorder (PTSD), however, several studies have demonstrated the association between bullying (including those being the bully, victim) and PTSD. The aim of the present study was to investigate the relationship between bullying and PTSD and suicide attempts among adolescents across nine countries. A total of 4051 adolescents with a mean age of 14.9 years found that 36.6% of the adolescents reported exposure to bullying. There were some gender differences across countries. Bullying was significantly associated with PTSD symptoms and suicide attempts among the adolescents. National prevention plans and interventions are needed to prevent bullying.